Electrocardiographic Evaluation in Athletes and Use of the Seattle Criteria to Improve Specificity - Lisman, Kevin A. (Methodist Debakey Cardiovasc J, 2016)
The screening of athletes for cardiovascular disease prior to participation can be challenging. Sustained training often leads to anatomical changes in the heart that can translate into electrocardiographic (ECG) abnormalities. This can lead to a high false-positive rate that excludes healthy participants or results in costly workups. The Seattle Criteria applied to ECG interpretation has resulted in improved specificity without sacrificing sensitivity. At the Houston Methodist DeBakey Heart & Vascular Center in Houston, we have had much success using this tool to screen thousands of athletes ranging across all age groups and levels of expertise—from the middle school level to the professional athlete.